The concept of mRNA abundance classes: a critical reevaluation. - Quinlan, T J (1978)
Derivative plots have been constructed for hybridization reactions between polysomal poly(A)-containing RNA and oligo(dT)-primed cDNA. In one method the derivative was calculated directly from the data, and in the other, from a non-linear least squares fit using 9-10 ideal components. In some cases these methods yield very similar results and strongly suggest that the hybridization data support discrete components. Reactions with two and four major components indicate that the often-reported three abundance class model is only one of several possibilities for eukaryotic cells. In other situations neither method strongly suggests the presence of discrete components (in one case even after enrichment of the cDNA population by kinetic fractionation), implying that the components are closely spaced or that the entire mRNA population of those cells may not exist as discrete abundance classes. The universal occurrence of discrete abundance classes should be critically reexamined.